Think differently, think from arts - Sandoval Mota, Jairo Vladimir (Disertaciones, 2022)
In this article we elaborate a reflection on Art as a productive activity, starting from the philosophical contributions of Deleuze and Guattari, carrying out an analysis of their ontological conception characterized as a thought of difference, in order to point out the links that are established between philosophy and art. For this, we begin with a brief introduction where we frame the proposal of Deleuze and Guattari, emphasizing the "reversal of Platonism", which will be of special importance with regard to the new conception of art that the authors will propose. Then, in a general way, we analyze what it means to philosophize in the light of such project. Next, we address the issue of art, analyzing this field as an activity that implies thinking and producing difference. We end with some brief conclusions in which we point out that art, like philosophy, creates new territories and opens up new possibilities of life.